2020
DOI: 10.1080/03019233.2019.1709699
|View full text |Cite
|
Sign up to set email alerts
|

Assessment on the effect of unburned pulverized coal on the properties of coke in blast furnace

Abstract: The influence of anthracite unburned pulverized coal (AUPC) on the properties of coke at high temperature was studied using the thermogravimetric equipment. The micro morphology and mineral transformation were analyzed by scanning electron microscope with energy spectrum (SEM-EDS) and X-Ray diffracton (XRD) in present research. The results show that CO 2 preferentially reacts with AUPC, making SiC easier to form and wet the slag, which can enter pores and passivate gas from entering. Meanwhile, AUPC ash genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A study on anthracite showed that CO 2 preferentially reacts with char, adhered to the coke surface, making SiC easier to form and wet the slag, which can enter pores and passivate gas from entering. The ash wetting and catalysis of iron or CaO might shift inner-pore gasification to the outside and delaying or suppress the degradation of the coke [4].…”
Section: Char Behaviour Outside the Racewaymentioning
confidence: 99%
See 1 more Smart Citation
“…A study on anthracite showed that CO 2 preferentially reacts with char, adhered to the coke surface, making SiC easier to form and wet the slag, which can enter pores and passivate gas from entering. The ash wetting and catalysis of iron or CaO might shift inner-pore gasification to the outside and delaying or suppress the degradation of the coke [4].…”
Section: Char Behaviour Outside the Racewaymentioning
confidence: 99%
“…About 65% of blast furnaces worldwide operate using the injection technology. PC is the most commonly used injectant: nearly 50% of blast furnaces worldwide operate with PC or about ¾ of BFs with injectants, thereunder all the blast furnaces in Japan, all modern blast furnaces in China and the majority of blast furnaces in EU [3,4]. The key trend is increasing PC injection rates; over 200 kg tHM −1 PC on an annual basis is no rarity anymore [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars at home and abroad have performed a lot of research on the behavior of UPC in BF. For example, Li et al [11] and Xiang et al [12] found that CO 2 will react with UPC first, and then coke. Chai et al [13] explored the influence of UPC on the gasification reaction of coke in BF, and the results showed that, in the soft melting zone, the gasification reaction model of coke blocks attached to the UPC corresponded to an unreacted core model and a porous volume-reacted model, jointly.…”
Section: Introductionmentioning
confidence: 99%
“…Coke plays the role of a reductant, carburizer, heat source, and structural support in a blast furnace. 20,21 Unfortunately, the quantitative proportion of the four roles has been less studied. Up to now, the behavior and performance of the hearth deadman coke have not been directly observed and detected.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al proposed the carbon dissolution–graphite precipitation mechanism to explain the iron catalytic graphitization process by experimentally investigating at 1100, 1200, 1300, and 1500 °C. Coke plays the role of a reductant, carburizer, heat source, and structural support in a blast furnace. , Unfortunately, the quantitative proportion of the four roles has been less studied. Up to now, the behavior and performance of the hearth deadman coke have not been directly observed and detected.…”
Section: Introductionmentioning
confidence: 99%